A simple versatile solution for collecting multidimensional clinical data based on the CakePHP web application framework - Biermann, Martin (Computer methods and programs in biomedicine, 2014)
Clinical trials aiming for regulatory approval of a therapeutic agent must be conducted according to Good Clinical Practice (GCP). Clinical Data Management Systems (CDMS) are specialized software solutions geared toward GCP-trials. They are however less suited for data management in small non-GCP research projects. For use in researcher-initiated non-GCP studies, we developed a client–server database application based on the public domain CakePHP framework. The underlying MySQL database uses a simple data model based on only five data tables. The graphical user interface can be run in any web browser inside the hospital network. Data are validated upon entry. Data contained in external database systems can be imported interactively. Data are automatically anonymized on import, and the key lists identifying the subjects being logged to a restricted part of the database. Data analysis is performed by separate statistics and analysis software connecting to the database via a generic Open Database Connectivity (ODBC) interface. Since its first pilot implementation in 2011, the solution has been applied to seven different clinical research projects covering different clinical problems in different organ systems such as cancer of the thyroid and the prostate glands. This paper shows how the adoption of a generic web application framework is a feasible, flexible, low-cost, and user-friendly way of managing multidimensional research data in researcher-initiated non-GCP clinical projects.